Correlates of success in family business transitions - Morris, Michael H.; Williams, Roy O.; Allen, Jeffrey A.; Avila, Ramon A. (Journal of Business Venturing, 1997)
Fundamental differences are identified between the nature and functioning of family-owned and -managed businesses and those that are not familu-controlled. These differences include the time horizons of management, the implications of business failure, the degree of job security, the centralization of decision-making, accountability for decision-making, and the impact of the family system on the business system, among others. It is argued that the most significant of these differences concerns the way in which executive succession occurs, and specifically, unique aspects of the process of intergenerational transfer within family-owned businesses. Based on an initial round of interviews with second- and third-generation family business owners, and a detailed review of the extant literature, a model is proposed consisting of three sets of determinants of successful family business transitions: the preparation level of the heirs, the nature of relationships among family members, and the types of planning and control activities engaged in by the management of the family business. Successful transitions are further hypothesized to influence subsequent company performance. Much of the research to date on family business transitions has tended to be qualitative, case-oriented, and/or anecdotal in nature. The result has been a number of rich insights into the complexities and dynamics of the family enterprise, but limited in terms of the generalizability of the findings. Considerably less attention has been devoted to quantitative studies that employ larger samples and provide empirical tests of relationships between key variables. This lack of attention is traced to inherent measurement difficulties in the family business field, and to the relatively young status of the field itself as a distinct area receiving academic attention. The current study attempts to bridge this gap. The study provides a quantitative assessment of the proposed model using two cross-sectional sub-samples consisting of 209 second- and third-generation family-owned businesses. Both regression and structural equations (LISREL) analyses are employed. The results indicate support for the proposed model. Family business transitions do occur more smoothly when heirs are better prepared, when relationships among family members are more trust-based and affable, and when family businesses engage in more planning for taxation and wealth-transfer purposes. Of these factors, relationships within the family has the single greatest impact on successful transitions. At the same time, smoother transitions do not necessarily result in better post-transition performance by the enterprise. This linkage to performance appears to be more complex. One possibility is that some level of conflict or strife is a prerequisite for the transition to have a significant impact on subsequent performance. Based on these results, family business owners are encouraged to devote relatively more attention to relationship issues, and relatively less to estate and tax planning. It is suggested that a “relationship charter” be developed as a vehicle for strategically managing relationships within the family, much as relationships must be managed with suppliers or customers. Suggestions are also made for further research, and the study's limitations are denoted. Researchers are encouraged to devote efforts to exploring relationships among the exogenous variables in the research model, such as that between preparation levels of heirs and family relationships. Further, the issue of success and failure in second- and third-generation businesses warrants greater attention, including identification of key failure and success factors as well as determination of differences in failure rates for family— versus non-family—owned businesses and isolation of the reasons for such differences.